Dynamics of the NbCl5‐Catalyzed Cycloaddition of Propylene Oxide and CO2: Assessing the Dual Role of the Nucleophilic Co‐Catalysts. Issue 37 (23rd July 2014) - D'Elia, Valerio; Ghani, Amylia A.; Monassier, Antoine; Sofack‐Kreutzer, Julien; Pelletier, Jeremie D. A.; Drees, Markus; Vummaleti, Sai V. C.; Poater, Albert; Cavallo, Luigi; Cokoja, Mirza; Basset, Jean‐Marie; Kühn, Fritz. E.
Abstract A mechanistic study on the synthesis of propylene carbonate (PC) from CO2 and propylene oxide (PO) catalyzed by NbCl5 and organic nucleophiles such as 4‐dimethylaminopyridine (DMAP) or tetra‐n‐butylammonium bromide (NBu4Br) is reported. A combination of in situ spectroscopic techniques and kinetic studies has been used to provide detailed insight into the reaction mechanism, the formation of intermediates, and interactions between the reaction partners. The results of DFT calculations support the experimental observations and allow us to propose a mechanism for this reaction.